Aplikasi rumus sinus kosinus pada segitiga bola dalam penentuan arah kiblat masjid di Kota Medan (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
Facing the Qibla towards the Ka'bah is one of the requirements for the validity of a prayer for Muslims. People in the area of ​​Mecca and around Saudi Arabia, they have  it easy to find out the position of the Qibla because there are still visible clues that can be used to determine the exact direction of the Qibla. Unlike people who are in areas that far from the Ka'ba and Arabia, geographic clues and exact directions are difficult to find, so a concept emerged that could help determine the direction of the Qibla. In Indonesia, prior to 2010, the direction of the Qibla was conveyed to the Indonesian people to be in the west direction, which was recently corrected back to the west-northwest direction. The determination of the Qibla  direction cannot be separated from the mathematical concept, and in this study we re-tested the use of the cosine  and sine formula in spherical triangle to determine the direction of the Qibla. It is hoped that by calculating and measuring the direction angle and the azimuth of the Qibla and the estimation of the number of mosques experiencing errors in that are not correctly facing the actual direction of the Qibla. In the city of Medan, it was found that the direction resulted from the calculation was 67 ° 14 'from north to the west or the azimuth qibla value is 292 ° 45' with an estimate that 54% of mosques in the city of Medan had a directional error that was still incorrectly facing the Qibla direction.
Keywords: qibla; spherical triangle; trigonometry